A Comparative Study on Sexual Function and Sexual Distress of Women With and Without Breast Cancer in Zanjan, Iran - Mina Esmkhani; Samaneh Youseflo; Mohsen Hosseinzadeh; Monireh Moharram Nezhad-Fard; Fateme Ghanbarpour; Effat Merghati Khoei (Iran University of Medical Sciences, 2023)
Background & Aims Breast cancer (BC) is one of the important challenges of the health system due to its impact on marital relationships. This study aims to compare sexual function and sexual distress of women with and without BC. Materials & Methods In this case-control study, 75 women with BC and 75 healthy women from Zanjan, Iran participated. Data were collected using a demographic form, the female sexual distress scale-revised (FSDS-R), and the female sexual function index (FSFI). Data analysis was done in SPSS software, version 20 using the Mann-Whitney test and multivariate analysis of covariance. Results The mean age of patients was 36.49±6.53 years and the mean age of controls was 36±0.72 years. There was no statistically significant difference between the two groups in terms of some demographic variables such as age, educational level of women and their husbands, occupation of women and their husbands, place of residence, and number of children (P>0.05). The mean score of FSFI in all subscales in the patient group was lower than in the control group. This difference was statistically significant only in the dimension of desire (P=0.003). regarding the sexual distress variable, the mean FSDS-R score of healthy women was lower than that of women with breast cancer, but this difference was not statistically significant (P>0.05). Conclusion The difference between women with and without breast cancer is significant only in the desire domain of sexual function. There is no statistically significant difference between the two groups in sexual distress and in other domains of sexual function. The sexual problems of women with BC require consideration and support, and provding counseling in terms of sexual function.